O capital social como um dos fatores de sustentabilidade de cooperativas agroindustriais, estudo de caso - Moreira, José César Pontes (2008)
The present work relates the presence of social capital as resource for the sustainability of agroindustrial cooperatives, with main focus in the state of Ceará. It is verified the way the social capital, having as sources the confidence, associativism, cooperation, participation, and collective action, contributes with the performance of the analyzed co-operatives. It was used the case study of two agro-industrial cooperatives: COOPEMOVA and COCEDRO. Then it was estimated the social capital index of each cooperative and the data were gathered through observation in tje ambience of the cooperatgives and the application of two questionnaires. It was só worked out an analysis of the cooperates quality of life. We made sure in this work, just as we hoped for, that the COOPEMOVA, which holds the highest level of social capital, was also the one which sjowed the highest level of satisfaction and lilfe quality of the cooperates. On the other hand, it was concluded that the COCEDRO holds a lower level of social capital and satisfaction of the cooperates. Such results corroborate the proposition that the social capital is fundamental for the maintenance of agro-industrial cooperatives. It was noticed, after all, that a simple existence of the social capital doesn't solve all the problems. Nevertheless, its directioning towards action and combining with other resoources may contribute, a great deal, with the productive and social outcome of agro industrial cooperatives, which generates a sustainable economical development for the state or region.